The Effect of Stock Trading Volume, Inflation, Rupiah Exchange Rate, and Interest Rates on the Composite Stock Price Index (IHSG) 2022-2024 - Fareza Kusbari, Fiqih; Adib, Noval (Journal Research of Social Science, Economics, and Management, 2026)
The dynamics of the capital market in the post-pandemic era have become increasingly complex, influenced by both macroeconomic conditions and market activity. In Indonesia, fluctuations in the Composite Stock Price Index (IHSG)reflect changes in market liquidity and price stability, making it essential to understand the role of key economic indicators. This study aims to analyze the effect of stock trading volume, inflation, the Rupiah exchange rate, and interest rates on the movement of the Composite Stock Price Index (IHSG) during the period January 2022 to December 2024. This research employs a quantitative approach using monthly secondary data consisting of 36 observations obtained from the Indonesia Stock Exchange, Bank Indonesia, and the Central Statistics Agency. Data analysis was conducted using multiple linear regression, supported by classical assumption tests to ensure the validity of the model. The results of the study indicate that stock trading volume has a positive and significant impact on the Composite Stock Price Index (IHSG). Conversely, inflation has a negative and significant impact on the index. However, the Rupiah exchange rate and interest rates did not show a significant partial impact on the movement of the Composite Stock Price Index (IHSG) during the study period. In conclusion, the movement of the Indonesian stock market in the post-pandemic period is primarily influenced by liquidity and inflation stability. These findings highlight the importance of maintaining stable economic conditions and active market participation to support sustainable capital market growth.